Editorial: The “poly-periphery” and the “peripheral turn” in urban studies - Richmond, Matthew A.; Jesus, Patrícia Maria de; Legroux, Jean [UNESP] (Revista Brasileira de Estudos Urbanos e Regionais (RBEUR), 2025)
Editorial: The “poly-periphery” and the “peripheral turn” in urban studies